Fibromyalgia diagnosis from a multi-omics approach: a gut feeling - Durán-González, Elena; Ramírez-Tejero, Jorge Antolín; Pérez-Sánchez, Marta; Morales-Torres, Carmen; Gómez-Morano, Rosa; Díaz-López, Claudia; Martínez-Lara, Antonio; Cotán, David (Frontiers in Microbiology, 2025)
BackgroundFibromyalgia is a complex disorder whose main symptoms are chronic widespread pain and fatigue and affects between 0.2 and 6.6% of the world population. Nowadays, there are no molecular biomarkers that could facilitate diagnosis. The latest efforts by researchers have focused on studying problems at the level of central nervous system sensitivity, inflammation, and oxidative disorders.MethodsA total of 892 women were initially enrolled in the study. For individuals who met the inclusion criteria, a plasma proteome analysis was conducted using blood samples. Briefly, blood was collected, centrifuged, and analyzed by liquid nano-chromatography coupled to tandem mass spectrometry. After the raw data analysis, proteins with statistically significant differential abundance and a fold change over 1.2 (20% increase in fibromyalgia compared with control samples) or under 0.8 (20% decrease in fibromyalgia compared with control samples) in fibromyalgia were selected. For fecal metagenome analysis, fecal samples were collected and processed for DNA extraction. Amplicon sequencing of V3–V4 regions from the 16S ribosomal RNA gene was performed using the Illumina MiSeq platform. The statistical analysis was conducted using R v4.3.2 base packages.ResultsAfter applying exclusion criteria, 242 women (199 patients and 43 age- and environmentally paired controls) provided plasma and feces samples, as well as properly filled health questionnaires. A total of 30 proteins and 19 taxa were differentially expressed in fibromyalgia patients, and their integration into an algorithm allows for discrimination between cases and controls. The multi-omic approach for biomarker discovery in this study proposes a multifactorial connection between gut microbiota and mitochondria-derived oxidative stress and inflammation.ConclusionsPlasma and fecal multi-omics analysis suggest an intricate and multifactorial connection between gut microbiota and mitochondria-derived oxidative stress and inflammation in FM patients, with glyceraldehyde-3-phosphate dehydrogenase and Streptococcus salivarius as leading actors.Trial registrationNCT05921409.